A theory of unborn life from abortion to genetic manipulation - Karnein, Anja J. (New York ; Oxford : Oxford University Press, 2012)
In light of biomedical technologies, such as artificial reproduction, stem cell research, and genetic selection, the question of what we owe to future persons is as contested as ever. Here, Karnein provides a novel theory that shows how our commitments to persons can help us make sense of our obligations to unborn life.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: Unborn children (Law); Genetic engineering -- Law and legislation; Bioethics; Fetus -- Legal status, laws, etc. -- United States; Fetus -- Legal status, laws, etc. -- Germany